Peran Dewan Kehormatan Daerah Dalam Menegakan Sanksi atas Pelanggaran Kode Etik - Hestiana Puspitasari (Kampus Akademik Publiser, 2024)
This research aims to understand and analyze the forms of guidance, supervision, and enforcement of sanctions against Notaries proven to have violated the code of ethics. The problem statement consists of how the guidance and supervision of Notaries regarding ethical code violations are conducted, and how sanctions are enforced by the Regional Council of Honor for ethical code violations by Notaries. This study is a normative legal research strengthened by field data, examining legislation regarding the researched issues, as well as interviews to support the research findings. The results of this thesis show that the supervision conducted by the Council of Honor is an internal monitoring mechanism established by the Indonesian Notary Association (INI), where both preventive and repressive forms of supervision and guidance are implemented. Preventive measures involve providing guidance during inspections of Notaries, while repressive measures involve sanctioning Notaries. Sanctions imposed on Notaries proven to have violated the code of ethics are tailored to the type and quantity of the violation. Sanctions can be imposed on Notaries as long as a report is received by the Council of Honor. If a Notary is found not to have committed a violation, based on the recommendation of the Regional Council of Honor, the Regional Executive Board may issue a statement declaring that the concerned Notary has never violated laws related to their duties and responsibilities.